George Kaufman portrait - Ben Solowey:::Creator::::::::::::
A portrait of George Kaufman. On the back it reads " The Studio of Ben Solowey (1900-1978) George Kaufman, drawn from life by Ben Solowey" George Kaufman worked with John Steinbeck on the play "Of mice and men." RESTRICTED USE